Best Practices for Computational Science: Software Infrastructure and Environments for Reproducible and Extensible Research. Issue 1 (9th July 2014) - Stodden, Victoria; Miguez, Sheila
The goal of this article is to coalesce a discussion around best practices for scholarly research that utilizes computational methods, by providing a formalized set of best practice recommendations to guide computational scientists and other stakeholders wishing to disseminate reproducible research, facilitate innovation by enabling data and code re-use, and enable broader communication of the output of computational scientific research. Scholarly dissemination and communication standards are changing to reflect the increasingly computational nature of scholarly research, primarily to include the sharing of the data and code associated with published results. We also present these Best Practices as a living, evolving, and changing document athttp://wiki.stodden.net/Best_Practices .